Fabrication of S-scheme hollow TiO2@Bi2MoO6 composite for efficiently photocatalytic CO2 reduction. (January 2023) - Ren, Guangmin; Wei, Zixuan; Li, Zizhen; Zhang, Xiaochao; Meng, Xiangchao
Abstract: Herein, an S-scheme hollow TiO2 @Bi2 MoO6 heterojunction was synthesized for photocatalytic reduction of CO2 under simulated sunlight. Among all prepared composites, the TiO2 @Bi2 MoO6 with 20% of TiO2 exhibited the highest CO yield (183.97 μmol/g within 6 h), which was 4.0 and 2.4 times higher than pristine TiO2 and Bi2 MoO6, respectively. The improved photocatalytic activity may be due to the formation of S-scheme heterojunction to promote the separation and transfer of photogenerated charge carriers. Additionally, this hollow structure provided abundant sites in terms of CO2 adsorption and activation. Meanwhile, the photogenerated charge transfer mechanism of the S-scheme was verified by work function calculations, Electron paramagnetic resonance (EPR) measurements as well as X-ray photoelectron spectroscopy (XPS). This research presents a novel approach to improve photocatalytic reduction of CO2 via morphology modulation and the fabrication of S-scheme heterojunction. Graphical abstract: Image 1 Highlights: S-scheme hollow TiO2 @Bi2 MoO6 heterojunctions were prepared. High yields of CO were achieved. S-scheme heterojunction improved charge separation. Both experimental and DFT calculations proposed the possible S-scheme mechanism.